Hábitos alimenticios y aspectos del uso del hábitat por el chivo cabezón Ariopsis sp. (aff. assimilis) (Siluriformes: Ariidae), en una laguna costera neotropical (Ecorregión Darién, Colombia) (2015)
ABSTRACT: The New Granada sea cat sh, Ariopsis sp. (aff. assimilis) is a species endemic to the Colombian Caribbean coast and the western coast of Venezuela, but it is endangered due to pressures from artisanal shing. Diet and aspects of habitat use were studied through its spatial and temporal distribution patterns (density and biomass) in a coastal estuary along an environmental gradient de ned by the turbid plume of the Turbo River (Darien Ecorregion). The largest sized fish fed mainly on fish, anomuran crustaceans and shrimps, exhibiting a tendency for a generalist diet, while the smaller sh fed mainly on copepods, being specialist feeders, indicating an ontogenic change in the diet of this population. We hypothesize that this species may present patterns of distribution and habitat use in a sequential form in time and space, or seasonal programming. The southern part of the of the estuary may play an important role in reproduction as habitat for the larger fish, which brood eggs mainly during the dry season, while the middle and northern zones, bordered by mangroves, may be important nursery areas, with larger peaks in abundance of smaller sh mainly during the rainy season.